ROOTSTOCK QUALITY INFLUENCE VINEYARD VITALITY IS AND ON YIELD - Teona Dolidze (Innovate Conferences, 2025)
Present Research Aim Aim Rootstock Material Qualitative Settings Critical Influence Analysis Vitis vinifera - Long-term Productivity And Agroecological With stress factors Adaptation . Rootstock Genetic , physiological And Agronomic Features Causes Vine Roots System efficiency , which It is crucial. Harvest Quantity And On the quality of Georgia , as Viticulture Region In context , let's study Imereti And West Georgia Nursery Principles of farm operations.
Keywords: vine rootstock ; viability ; grafting Quality; Phylloxera .